Analisa Dampak Keberadaan Safari Lagoi terhadap Pariwisata di Kawasan Wisata Terpadu - Minarni Anita Gultom; Susetyo Rohadi; Dion Dewanto T; Maria Regina Nansi (Jurnal Informatika Ekonomi Bisnis, 2023)
Safari Lagoi is a 8 year old tourism destination in an integrated tourism area Bintan Resort. The good fact can be found that Safari Lagoi had atracted almost 4,000 tourists in 2018 that increased significantly to 30,000 tourists in 2019. As a part of an integrated tourism destionation in Bintan Resort, Safari Lagoi gives a positive impact both direct or indirectly to the existing stakeholders. Thus, it is important to do an observation upon the correlation and impact that arise in this area. This impact analysis reletad to dual role of Safari Lagoi as tourism destination as well as nature conservation. Observation used is an analyses of primary and secondary data, includes tourists visiting data, investment, using quetionair and/or direct interview to get a feedback that will be analysed using SWOT to identify strategic recommendation for further development of Safari Lagoi. Bintan Resort has a big potential for ecotourism. The presence of Safari Lagoi offer a special attractiveness for tourists with their Flora and Fauna concervation and can become a key driver for ecotourism development in this integrated area. Safari Lagoi gives a positive impacts towards economy, social and culture, and environment. Safari Lagoi needs to make use the momentum of high tourists' animo and other stakeholder's positive feedback to expedite further development through good synergy with Bintan Resorts Master Developer.